Patient-Reported Outcomes in Cosmetic Oculofacial Plastic Surgery: A Systematic Review. (December 2013) - Ramey, Nicholas A.; Burkat, Cat N.; Butt, Zeeshan; Lucarelli, Mark J.; Rose, John G.
Introduction: This work reviews the current state of patient-reported outcomes research in periocular cosmetic plastic surgery. Materials and Methods: A systematic review of the English-language medical literature from January 1946 through March 2013 was conducted for patient-reported outcomes measures used in periocular cosmetic plastic surgery patient populations. These measures were assessed for adherence to minimum standards recommended by the International Society for Quality of Life Research. Results: Thirteen outcome measures were identified. Upper-lid blepharoplasty was the only procedure for which an instrument, the Blepharoplasty Outcomes Evaluation, had been formally developed in the target patient group (periocular cosmetic surgery), and that met or exceeded minimum standards of reporting. Nine formally developed instruments were identified in the following applications: general facial cosmetic surgery (instruments that may be applied to periocular surgery, which are not restricted to any single facial intervention or anatomic region), chemodenervation, filler, and skin treatment. Of these, 5 instruments met minimum standards. Conclusions: Few well-developed, patient-reported outcomes measures targeted at periocular cosmetic patients exist at this time.